SUN-LB086 Hypercalcemia in Metastatic Cholangiocarcinoma Due to Coexisting Elevated Parathyroid Hormone Related Protein (PTHrP) and 1,25-Dihydroxy Vitamin D (Calcitriol): A Case Report - Sharma, Rajeev (J Endocr Soc, 2019)
Background: Hypercalcemia due to cholangiocarcinoma is not common. However, it is rarer to have both calcitriol and PTHrp mediated humoral hypercalcemia of malignancy Clinical Case: A 68 year old woman presented to a tertiary care cancer center after a CT scan for abdominal pain showed a large mass involving the right lobe of the liver extending into the porta hepatis with multiple low attenuation lesions scattered in the right and left lobe. Pancreas and gallbladder were normal. A liver biopsy was consistent with intrahepatic cholangiocarcinoma that was positive for CK7 and negative for CK 20, CD-X2, HepPar-1,TTF-1, Napsin-A, GATA-3, WT-1 and ER. Prior colonoscopy did not show evidence of adenocarcinoma. At baseline carbohydrate antigen (CA) 19-9 was mildly elevated (75 U/mL). Her initial biochemical abnormality was hypercalcemia (12.2 mg/dL, normal 8.4-10.2) along with elevated alkaline phosphatase (288 IU/L, normal 38-126). Parathyroid hormone (PTH) was low [6.6 pg/ml, normal 8.7-77.1] suggesting non-PTH mediated hypercalcemia. Parathyroid hormone related peptide (PTHrP) was normal [<1.1 pmol/L, normal <2] and early in treatment 1, 25- dihydroxyvitamin D (calcitriol) was high normal [75.7 pg/mL, normal 19.9-79.3]. She was started with gemcitabine and cisplatin for 3 cycles but changed to 2(nd) line oxaliplatin because of progression of disease with appearance of multiple pulmonary nodules and increased in size and number of multifocal cholangiocarcinoma masses and marginally increased abdominal/retroperitoneal adenopathy on CT scan about 3 months after initial chemotherapy. Her 2(nd) line treatment was stopped after 4 cycles because of further progression of disease on imaging. As her primary malignancy progressed, the levels of 1, 25 dihydroxyvitamin D (123 pg/mL) and PTHrP (3.8 pmol/L) became elevated. She was treated multiple times with IV fluids, zoledronic acid and denosumab. She was evaluated for a clinical trial but was unable to enroll because of persistent hypercalcemia. With options running out, she was started on PD-1 inhibitor pembrolizumab for 3 cycles. Unfortunately, her disease continued to progress with extensive liver metastasis and peritoneal carcinomatosis and increases in CA-19.9 (838 U/mL) and referred for hospice care. Her hypercalcemia continued to progress and at the time of hospice referral, her serum calcium was 13.6 mg/dL. Conclusion: Health care providers especially oncologists should be aware of humoral hypercalcemia of malignancy mediated by both calcitriol and PTHrp in cholangicarcinoma. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.